MODEL ARSITEKTUR POHON BERDASARKAN FUNGSI KAWASAN DI SMAN 2 BANJARBARU - Bara Sukma Fajar; Gusti Muhammad Hatta; Adistina Fitriani; Wahyuni Ilham (Jurnal Sylva Scienteae, 2021)
The tree architecture model in the education area is an example of modeling in overcoming noise and pollution problems. This school area is the object of research which aims to identify the building blocks of vegetation, calculate noise levels and formulate tree architectural designs at SMA N 2 Banjarbaru in structuring tree architectural models. This school, which is strategically located in the middle of Banjarbaru city, is classified as an area with dense vegetation which is directly supported by the presence of an urban forest. The architectural model is a reference for ecological and extrinsic improvement in SMA N 2 Banjarbaru. Vegetation identification and tree architecture models use descriptive analysis methods adapted to the spatial layout and building functions based on aesthetic, comfort and ecological values. The results of this study are there are architectural models or tree branching types known to be 10 types of architectural models from 41 types of vegetation in the form of tree species and shrubs. The highest noise reaches 70.4 dBA and the lowest is 37.8 dBA with an average of 20 vehicles passing. The formulation of model architectural designs consists of 5 types of architectural models, namely the Troll, Scarrone, Roux, Stone and Aubreville models which are adapted to the designated conditions of the area at SMAN 2 Banjarbaru which are expected to support educational activitiesModel arsitektur pohon pada kawasan pendidikan menjadi contoh permodelan dalam mengatasi masalah kebisingan dan polusi.  Kawasan sekolah ini menjadi objek penelitian yang bertujuan untuk mengidentifikasi struktur penyusun vegetasi, menghitung tingkat kebisingan dan merumuskan rancangan arsitektur pohon di SMA N 2 banjarbaru dalam penataan model arsitektur pohon. Sekolah yang terletak strategis di tengah kota Banjarbaru ini tergolong kawasan dengan padat vegetasi yang didukung langsung dengan adanya hutan kota. Model arsitektur menjadi acuan peningkatan ekologi maupun ekstrinsik di SMA N 2 Banjarbaru. Identifikasi vegetasi dan model Arsitektur pohon tersebut menggunakan metode analisis deskriptif yang disesuaikan dengan tata ruang dan fungsi bangunan berdasarkan nilai estetika, kenyamanan dan ekologi.  Hasil penelitian ini terdapat model arsitektur atau jenis bercabang pohon yang diketahui 10 jenis model arsitektur dari 41 jenis vegetasi berupa jenis pohon dan perdu. Kebisingan tertinggi mencapai 70,4 dBA dan terendah 37,8 dBA dengan rata-rata kendaraan yang melintas sebanyak 20 kendaraan. Rumusan rancangan arsitektur model sebanyak 5 jenis arsitektur model yaitu model Troll, Scarrone, Roux, Stone dan Aubreville yang disesuaikan dengan kondisi peruntukan area di SMAN 2 Banjarbaru yang diharapkan dapat menunjang aktivitas pendidikan